Endoscopic papillectomy and KRAS expression in the treatment of adenoma in the major duodenal papilla. (November 2015) - Haraldsson, Erik; Swahn, Fredrik; Verbeke, Caroline; Mattsson, Johanna S.M.; Enochsson, Lars; Ung, Kjell-Arne; Lundell, Lars; Heuchel, Rainer; Löhr, J.-Matthias; Arnelo, Urban
Abstract Objective. The use of endoscopic papillectomy for resecting adenomas in the major duodenal papilla is increasing. This study focuses on the following three issues: Can endoscopic papillectomy be performed as a safe diagnostic and/or therapeutic procedure in biopsy-verified or suspected ampullary adenoma? Does expression of mutated KRAS in resected adenomatous tissue predict long-term outcome? What other factors may affect long-term outcome and should, therefore, be considered in decision making prior to endoscopic papillectomy? Material and methods. Thirty-six prospectively collected patients who underwent endoscopic papillectomy at Karolinska University Hospital between 2005 and 2014 were analyzed. Results. The rate of exact agreement between the histomorphological grading of the endoscopic biopsies and the papillectomy specimens was low (48%). Obstructive jaundice at presentation increased the risk of undetected adenocarcinoma (RR = 3.98; 95% CI = 1.46–10.85, p = 0.007). Lesions with malignancies were significantly larger (mean 30.6 mm) than those where only adenomas were found (mean 14.4 mm, p = 0.001). Mutated KRAS was detected in 9 of the 36 post-papillectomy specimens, including 4 of the 5 cases of ampullary adenocarcinoma. Eighteen cases were endoscopically cured after a mean follow-up period of 47 months (range 16–92 months). Conclusions. Endoscopic papillectomy is a valuable staging tool because of the limitations of endoscopic biopsy. Endoscopic papillectomy concomitantly offers a curative treatment for most patients with adenoma in the major duodenal papilla. Jaundice at presentation and large adenomas may indicate the presence of more advanced disease. Determination of mutated KRAS seems to be of limited value in predicting long-term outcome.